YUGI’S CONCEPT OF GUNMAM PATIENTS REPORTING AT AYOTHIDOSS PANDITHAR HOSPITAL, NATIONAL INSTITUTE OF SIDDHA (NIS) - A CROSS SECTIONAL STUDY (International Journal of Ayurveda and Pharma Research, 2019)
According to Siddha system of medicine disease are numbered as 4448. One among them is Gunmam. Severe pain in the abdomen occurs as one of the symptoms and this makes the patient to bend forward in order to get relief from pain and hence the name is mentioned as Gunmam. As per sage Yugi, Gunmam is further classified into 8 types. The human body runs on the basis of Vatham, Pitham, Kabam and due to changes in the equilibrium of tri-dosha mankind acquires disease. As per Theraiyar Gunmam occurs due to vitiation of Vali thathu. Common symptoms of Gunmam are indigestion, vomiting, abdominal pain, abdominal distension, decrease body weight, loss of confidence. The signs and symptoms of Gunmam can be correlated to Acid Peptic Disease (APD). This study was undertaken to assess the incidence of different types of Gunmam patients reporting at OPD of Ayothidoss Pandithar Hospital. This is hospital based cross sectional study conducted in Ayothidoss Pandithar Hospital between months of May 2019 and July 2019. The study was given ethical approval by institutional Ethics Committee. The study included the completion of questionnaire which focuses on symptoms of eight types of Gunmam, thega ilakkanam, behavioural risk factors for Gunmam and physical measurements from randomly selected patients reporting to the OPD. Using Systematic random sampling method, 250 patients were selected from the OPD of Ayothidoss Pandithar Hospital. Statistical analysis was done using SPSS software. Among 250 Gunmam patients, 33.2% of subjects are Pitha thegi, 32.8% of subjects are Eri gunmam.